METHODOLOGY AND EDUCATIONAL TECHNOLOGIES FOR TEACHING LATIN. - Inoyatov Abdugani Abdufattaxovich (TADQIQOTLAR.UZ, 2024)
Annotation. This article explores various methodologies and educational technologies for teaching Latin. It aims to identify effective approaches and tools that enhance students' understanding and engagement. The study reviews traditional and modern teaching methods, evaluates digital resources, and provides practical suggestions for educators.